Isolation and identification of listeria monocytogenes from raw vegetables in Kuching and Kota Samarahan, Sarawak - Ardianshah, Bin Amirudin. (Universiti Malaysia Sarawak (UNIMAS), 2011)
L. monocytogenes is an opportunistic intracellular pathogen that has become an important cause of human foodbome infections worldwide. In this study, L. monocytogenes was isolated and identified from raw vegetable samples. Four main vegetables (cucumber, cabbage, winged bean and carrot) studied were purchased from upermarkets and wet markets in Kuching and Kota Samarahan area. The technique involved in the methodology used were enrichment with BLEB, followed by isolation on PALCAM agar and CHROMa gar Listeria, culturing on TSA and finally identification by Gram staining and conventional biochemical tests. Based on isolation of L. monocytogenes on PALCAM agar, the occurrence percentage of the bacteria differed slightly between the samples from supermarkets and wet markets in Kuching and Kota Samarahan which are 32.5% and 33.75%, respectively. However, following isolation on CHROMagar Listeria, only six positive results (7.5%) were obtained from both supermarket and wet market. Conventional biochemical te t were performed to further identify the presumptive colonies. MR-VP test, motility test and Gram staining gave positive results but indole test and H2S production test shown negativity.